Augmented Reality Support for Oncological Neurosurgery - de Freitas, Ana Clara Carneiro; e Silva, Beatriz Muniz de Castro; Bernardino, Beatriz Rianho; Boriero, Gabriela Moreno; Barbosa, Marcio Tiago de Oliveira; Chojniak, Rubens; Soares, Luciano Pereira (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
This project aims to enhance oncological neurosurgery by displaying brain tumors using Augmented Reality (AR) as an overlay image during surgical procedures. Its purpose is to assist neurosurgeons in tasks such as brain biopsies by providing a clear and precise visualization of the affected area, thus enabling faster and less invasive surgeries, ultimately offering a more comfortable experience for patients. Currently, medical procedures achieve this through neuronavigation systems, which display two-dimensional images of the patient’s brain on a screen, typically positioned beside the patient or in separate imaging support rooms. By utilizing AR, surgeons can directly visualize the tumor on the patient’s body through a virtual 3D model, eliminating the need to frequently refer to external images. This project was developed using Microsoft HoloLens, a specialized AR headset, and Unity, a game engine widely used for 3D environment development. The system uses DICOM files as input, which are converted into 3D objects displayed through the AR headset.